Mutations of human NARS2, encoding the mitochondrial asparaginyl-tRNA synthetase, cause nonsyndromic deafness and Leigh syndrome. - Mariella Simon; Elodie M Richard; Xinjian Wang; Mohsin Shahzad; Vincent H Huang; Tanveer A Qaiser; Prasanth Potluri; Sarah E Mahl; Antonio Davila; Sabiha Nazli; Saege Hancock; Margret Yu; et al. (PLoS Genetics)
Here we demonstrate association of variants in the mitochondrial asparaginyl-tRNA synthetase NARS2 with human hearing loss and Leigh syndrome. A homozygous missense mutation ([c.637G>T; p.Val213Phe]) is the underlying cause of nonsyndromic hearing loss (DFNB94) and compound heterozygous mutations ([c.969T>A; p.Tyr323*] + [c.1142A>G; p.Asn381Ser]) result in mitochondrial respiratory chain deficiency and Leigh syndrome, which is a neurodegenerative disease characterized by symmetric, bilateral lesions in the basal ganglia, thalamus, and brain stem. The severity of the genetic lesions and their effects on NARS2 protein structure cosegregate with the phenotype. A hypothetical truncated NARS2 protein, secondary to the Leigh syndrome mutation p.Tyr323* is not detectable and p.Asn381Ser further decreases NARS2 protein levels in patient fibroblasts. p.Asn381Ser also disrupts dimerization of NARS2, while the hearing loss p.Val213Phe variant has no effect on NARS2 oligomerization. Additionally we demonstrate decreased steady-state levels of mt-tRNAAsn in fibroblasts from the Leigh syndrome patients. In these cells we show that a decrease in oxygen consumption rates (OCR) and electron transport chain (ETC) activity can be rescued by overexpression of wild type NARS2. However, overexpression of the hearing loss associated p.Val213Phe mutant protein in these fibroblasts cannot complement the OCR and ETC defects. Our findings establish lesions in NARS2 as a new cause for nonsyndromic hearing loss and Leigh syndrome.